A Multi-method Investigation of the Personality Correlates of Functional Ability in Older Adults. Issue 4 (3rd July 2020) - Gogniat, Marissa A.; Hyatt, Courtland S.; Jean, Kharine R.; Rodriguez, Violeta J.; Robinson, Talia L.; Miller, Lloyd Stephen
ABSTRACT: Objectives: This study evaluated the role of personality in predicting functional ability (FA) in older adults using self-report, collateral report, and performance-based measures of FA. Methods: Participants included older adults (N = 131) who completed a personality measure (NEO-FFI), a self-report of FA (OARS ADL), and participated in a performance-based assessment of FA (DAFS-R). In addition, each participant had a collateral complete a collateral report of FA (OARS ADL). Bivariate correlations were computed to assess how Five Factor Model traits were related to self-report, collateral, and performance-based measures of FA. Results: Neuroticism was negatively related to self-reported FA ( r = − .27) and collateral-reported FA ( r = − .18) and Conscientiousness was positively related to self-reported FA ( r = .25). None of the traits were significantly related to the performance-based measure of FA. Conclusions: These results suggest that personality traits can impact self-reported FA in older adults and underscore the importance of assessing FA in older adults using multiple methods, particularly performance-based measures. Clinical Implications: Clinicians should consider how personality may impact FA in older adults and multiple methods of FA performance should be examined to better tailor recommendations.